Codes, Cryptology and Information Security: Third International Conference, C2SI 2019, Rabat, Morocco, April 22-24, 2019, Proceedings - In Honor of Said El Hajji - Carlet, Claude; Guilley, Sylvain; Nitaj, Abderrahmane; Souidi, El Mamoun (Lecture Notes in Computer Science, 2019)
This book constitutes the proceedings of the Third International Conference on Codes, Cryptology and Information Security, C2SI 2019, held in Rabat, Morocco, in April 2019. The 19 regular papers presented together with 5 invited talks were carefully reviewed and selected from 90 submissions. The first aim of this conference is to pay homage to Said El Hajji for his valuable contribution in research, teaching and disseminating knowledge in numerical analysis, modeling and information security in Morocco, Africa, and worldwide. The second aim of the conference is to provide an international forum for researchers from academia and practitioners from industry from all over the world for discussion of all forms of cryptology, coding theory, and information security.